Survival of patients with salivary gland malignancies depending on the molecular profile of the tumor - S. I. Kutukova; E. N. Imyanitov; G. A. Raskin; Yu. V. Ivaskova; N. P. Belyak; A. I. Yaremenko; A. Ya. Razumova; P. M. Baykalova (Опухоли головы и шеи)
Introduction. Standard methods of drug or radiation therapy administration for salivary gland cancer is the least successful for now. Therefore, the identification of new markers with morphological features is extremely necessary to improve the effectiveness of treatment and increase the survival rates of patients with this pathology.The study objective is to assess the prevalence of expression of HER2/neu, PD-L1, and RET mRNA in salivary gland malignancies and assess their impact on overall and disease-free survival.Materials and methods. Fifty-nine patients with a confirmed diagnosis of salivary gland cancer (stages II–IVA) were examined in the period from 2012 to 2014 at Saint Petersburg City Clinical Oncology Dispensary. All materials were subjected to immunohistochemical research to determine the expression of HER2, PD-L1 in tumor and immune cells, the CPS index was calculated, and the frequency of the mRNA gene RET expression using a real-time polymerase chain reaction was detected.Results. The overall survival of patients with mild and high HER2 expression was 41 months (95 % confidence interval (CI) 4.50–72.00), which is more than 4 time less than in patients with low or no expression (p = 0.00715). Significant differences were also received in the progression-free survival in the group of patients with negative or insignificant expression of HER2 receptors. The overall survival of patients with CPS >1 was 72 months (95 % CI 19.5–72.00) and significantly differed from the group of patients with CPS <1, where it was not yet achieved (p = 0.0124). mRNA expression of the RET gene was detected in 13 out of 48 cases, which was 27.08 %. The expression level ranged from 0 to 0.205. The progression-free survival in the group of patients with mRNA expression was 168 months (95 % CI 16.00–168.00) and tended to increase in the group of patients who did not have this expression.Conclusion. When analyzing the obtained data, it was proved that knowledge of the salivary glands malignant tumors receptor status become one of the factors in determining the prognosis of the disease, as well as a predictive factor of targeted drugs effectiveness (after сonducting prospective randomized studies).